Fluorescent EGTA-derived carbon dots for turn on–off–on detection of Fe3+ and ascorbic acid via hydrothermal synthesis and cellular imaging - Kanwal Iqbal; Anam Iqbal; Wenwu Qin; Muhammad Imran; Zeeshan Ajmal; Imran Khan; Guolong Xing (Scientific Reports)
Abstract We present a novel, one-step hydrothermal synthesis of carbon dots (CDs) with intense blue fluorescence and a remarkably high quantum yield of 50%, using ethylene glycol tetraacetic acid (EGTA) as a single precursor eliminating the need for additional passivation agents. This streamlined strategy represents a significant advancement in the efficient production of functional CDs. The resulting CDs exhibit dual-mode fluorescence sensing, selectively detecting Fe3+ through a fluorescence quenching mechanism, with an ultra-low detection limit of 23 nM. Notably, the quenched fluorescence is fully restored upon the introduction of ascorbic acid (AA), enabling a highly sensitive “off–on” detection system with a detection limit of 21 nM. This approach demonstrates excellent selectivity for AA over dopamine and other amino acids, providing a reliable method for distinguishing AA in complex biological matrices. Furthermore, the CDs-based Fe3+/AA sensing system proves highly effective for bioimaging applications, allowing for clear visualization of Fe3+ and AA in living cells. Compared to conventional commercial assays, this method is cost-effective, simple, and scalable, offering a powerful tool for next-generation biosensing and bioimaging. The fluorescence-based “off–on” mechanism, combined with the versatility of CDs in real-sample analysis, highlights the innovation and practical value of this approach.